A Powerful HPLC-ELSD Method for Simultaneous Determination of Fecal Bile Acids in T2DM Rats Interfered by Sanhuang Xiexin Tang. (2nd February 2021) - Chen, Mengjun; Liu, Chen; Shen, Yumeng; Zou, Junfeng; Zhang, Zhimiao; Wan, Yue; Yang, Lei; Jiang, Shu; Qian, Dawei; Duan, Jinao
Abstract: Bile acids (BAs) as important endogenous ligands can activate farnesoid X receptor (FXR) and G-protein-coupled bile acid receptor 1 (GPBAR1, also known as TGR5) signaling to regulate glycolipid metabolism. In this study, a simple, reliable and sensitive analysis method for simultaneous determination of four BAs from rat feces based on high-performance liquid chromatography with evaporative light scattering detector (HPLC-ELSD) was developed. Chromatographic analysis was performed with the mobile phases of acetonitrile and 0.2% formic acid. All the standard curves exhibited good linearity ( R 2 ≥ 0.99). The relative standard deviations of precision, stability and repeatability varied from 1.27 to 3.96%, 2.20 to 3.89% and 3.00 to 4.31%, respectively. The validated method was successfully applied to investigate the variation of four BAs in feces from T2DM rats after oral administration of Sanhuang Xiexin Tang (SXT). Data showed that SXT could remarkably increase the contents of conjunct BAs and decrease the contents of free BAs, which might contribute to ameliorate the symptoms of T2DM rats.